Agronomic characteristics and pollen morphology among tropical sweet corn hybrid varieties - Yong, Yan Shee (2023)
The development of local sweet corn hybrid varieties from the utilization of imported genetic materials would help to reduce reliance on imported seeds. In this study, five imported tropical sweet corn hybrid varieties were planted with Randomized Complete Block Design (RCBD) in Kampar, Perak to investigate their agronomic characteristics. The measured traits were analyzed using analysis of variance (ANOVA), followed by interpretation of their broad-sense heritability and phenotypic correlations. The results revealed that hybrid varieties GreenEagle 1602 Supersweet and Leckat 592 Sugar Rich with superior performance in pre- and post-harvest traits, relatively could be short-listed for the development of inbred lines. Broad-sense heritability (h2 B) estimates revealed from the variance components method were found high for total suspended solid (99.32%), ear height (98.75%), kernel length (98.53%), number of husks per ear (97.89%) and plant height (97.08%). Among the traits that were highly correlated to dehusked ear weight were dehusked dried ear weight (0.81), dehusked ear length (0.59), dehusked ear diameter (0.57), and number of husks per ear (0.54). For the selection purpose, the evaluated hybrid varieties with the iii highest number of husks per ear were suggested as the genetic material for yield improvement. Therefore, Leckat 592 Sugar Rich could be potential genetic resource for local inbred line development with the highest number of husks per ear (12.67 ± 0.19). On the other hand, the pollen grains from five different hybrid varieties were observed under a light microscope and scanning electron microscope (SEM). The morphology of pollen observed was circular and monoporate, and their size is approximately 100 μm, which their sizes and structure were found similar from both views. Collectively, these agronomic characteristics and pollen morphology could be acting as essential information for future study in optimizing production yield and assisting material for the identification of pollen development stages